552. Could Anticoagulant Use Prior to Infection with COVID-19 Decrease Mortality?. (31st December 2020) - Natali, Kayla M; Chan, Kok Hoe; Atallah, Liana; Nagarakanti, Sindhu; Slim, Jihad
Abstract: Background: The novel coronavirus (COVID-19) has resulted in substantial morbidity and mortality worldwide. Infection with COVID-19 has been associated with coagulopathy and inflammation. This prothrombotic state has been identified in the literature as an indicator of poor prognosis and those with COVID-19 who receive anticoagulation therapy may have better outcomes. Due to this prothrombotic state, patients who are currently receiving anticoagulation therapy for other indications prior to infection with COVID-19 may have better outcomes. Methods: This was a retrospective case control study conducted at an inner city hospital. Patients were eligible if they were hospitalized between March 15, 2020 and May 15, 2020 and had confirmed infection due to COVID-19. Patients were matched by age, sex, body mass index (BMI), diabetes mellitus (DM), hypertension (HTN) and estimated glomerular filtration rate (eGFR) by chronic kidney disease (CKD) state. This study evaluated morality in patients who were receiving long term anticoagulation therapy prior to infection with COVID-19 compared to those who were not. Results: Of the 436 patients hospitalized with confirmed infection due to COVID-19, 400 were eligible for analysis. Twenty-two were on anticoagulation therapy prior to admission. Among those patients, 68% were male and 32% were female. The majority of the patients were greater than 60 years of age (82%). Comorbidities were present in 21 patients and were as follows: HTN (95%), CKD (67%), DM (57%), obesity (36%). Of the 22 patients, five expired due to COVID-19 infection compared to 52 patients from the 149-patient matched cohort [z-score 1.13, p = 0.26; odds ratio (OR) 1.82; 95% confidence interval [CI], 0.69–4.71]. Conclusion: Prior long-term anticoagulation use does not appear to have a protective effect in patients with COVID-19 infection. Studies with larger sample size will be needed to answer this important question. Disclosures: Jihad Slim, MD, Abbvie (Speaker's Bureau)Gilead (Speaker's Bureau)Jansen (Speaker's Bureau)Merck (Speaker's Bureau)ViiV (Speaker's Bureau)